2015
DOI: 10.1116/1.4916575
|View full text |Cite
|
Sign up to set email alerts
|

Increased bismuth concentration in MBE GaAs1−xBix films by oscillating III/V flux ratio during growth

Abstract: Magnetic and transport properties of III-V based magnetic semiconductor (GaMn)As: Growth condition dependence Appl. Phys. Lett. 74, 398 (1999); 10.1063/1.123082 III-V based magnetic(GaMnAs)/nonmagnetic(AlAs) semiconductor superlattices Appl.The authors have examined bismuth concentration profiles in GaAs 1Àx Bi x films grown by molecular beam epitaxy using high angle annular dark field imaging (Z-contrast imaging) in an aberrationcorrected scanning transmission electron microscope in conjunction with x-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Profiles of the STEM image intensity along lines extending from the GaAs buffer layer were generated in the same way as described in Ref. [16]. The cross-sectional STEM sample was prepared by the wedge-polishing method, followed by Ar ion milling.…”
Section: Methodsmentioning
confidence: 99%
“…Profiles of the STEM image intensity along lines extending from the GaAs buffer layer were generated in the same way as described in Ref. [16]. The cross-sectional STEM sample was prepared by the wedge-polishing method, followed by Ar ion milling.…”
Section: Methodsmentioning
confidence: 99%
“…The GaAs 1−x Bi x films were grown at T g =320 °C with Bi beam-equivalent-pressures (BEP) of 1.2 ×10 −8 Torr and Ga and As 2 BEPs of 1.0×10 −7 Torr and 9.8×10 −7 Torr, respectively. The positions of the effusion cells in the MBE chamber cause a spatial variation in the fluxes such that the normalized Ga/As flux ratio varies approximately linearly across the 28 mm of potential growth surface from 0.77 in the As-rich region, to 1.77 in the Ga-rich region, as detailed in [5]. Growth inhomogeneities that might result typically are mitigated by substrate rotation.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on growth conditions, droplets of pure Bi or Ga-Bi have been observed on the surface of GaAsBi alloys [2][3][4]. It has been suggested that these droplets play a critical role in the incorporation of Bi into the film during growth [5]. Previous studies have largely focused on the composition and structure [3], and/or the connections between growth conditions and droplet formation [6][7][8].…”
mentioning
confidence: 99%
“…In 2015, Wood et al showed that oscillating flux ratios can produce enhanced Bi contents. [ 122 ] They attributed this to a periodic accumulation and crystallization of surface Ga droplets and a resulting vapor–liquid–solid incorporation pathway. This study was performed at 320 °C and observed average Bi contents of ≈3%—far lower than the limit imposed by the growth temperature (see Figure 7).…”
Section: Prospects For Improving Mbe Growthmentioning
confidence: 99%